Multidimensional Analysis of The Number of Deaths in European Countries During the Covid-19 Pandemic in Terms of Economic Security - Jarosław ZELKOWSKI; Bartosz KOZICKI; Jarosław TOMASZEWSKI; Grzegorz MIZURA (Communications of International Proceedings, 2021)
To carry out a multidimensional comparative analysis of the number of deaths in European countries during the COVID-19 pandemic in terms of economic security.  The subject of the study is 31 European countries while the object of the study of is the number of human deaths. The study formulates the Assumption -  following research question: Will the multidimensional comparative analysis of the number of human deaths during the COVID-19 pandemic in terms of economic security make it possible to predict the number of deaths in the future? The distribution of human deaths in 31 European countries considered on a weekly basis over a period from week 9 to week 16 of 2020 is normal. In all European countries which have been discussed, the COVID-19 pandemic has led to an increase in human deaths but the strength of the growth rate in each country is at different levels. Detecting upward trends in deaths in 2020 will change the regularity of human deaths from previous years (2017-2018) which, in turn, is likely to transfer to a reduction in the number of deaths in the future in proportion to their increase in 2020.The application of multidimensional comparative analyses of 31 European countries will allow the number of deaths of people to be predicted in the future in a dynamic way.
Keywords: Population; Deaths; Multidimensional Comparative Analyses; Economic Security.